PERSUASION STRATEGIES IN THE RECTOR'S SPEECH AT LAMBUNG MANGKURAT UNIVERSITY - Ardine, Lydia Sela (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA (JBSP), 2025)
AbstractPersuasion Strategies in the Rector's Speech at Lambung Mangkurat University. This research was conducted to understand persuasive communication strategies in higher education leadership context, particularly in the transformation era towards World Class University that demands institutional communication effectiveness. As the highest leader of higher education institutions, rectors have strategic responsibility to communicate university vision, mission, and policies to various stakeholders through speeches in academic forums. This study aims to elaborate the forms, patterns, and persuasion techniques used by Lambung Mangkurat University Rector in various speeches. This study adopts a descriptive qualitative approach to analyze persuasive rhetorical strategies in oral discourse delivered by ULM Rector. The primary data sources were speeches by ULM Rector for the 2022-2026 period collected from the university's official YouTube channel in various forums such as graduation ceremonies, new student orientation, and Dies Natalis. Data collection techniques included observation of speech recordings, transcript documentation, and audience interviews. Data analysis was conducted through data reduction, data presentation, and result verification stages. Research results show: (1) persuasion forms are reflected in balanced combination of ethos, pathos, and logos as the basis of rhetorical strategy; (2) speech composition patterns include problem-solving patterns, cause-effect patterns, pro-contra patterns, and motivated sequence patterns; (3) persuasion techniques include rationalization, identification, suggestion, and conformity adapted to audience characteristics and situational context. The research concludes that ULM Rector's speeches have high effectiveness in shaping audience opinions, directing thinking patterns, fostering attachment to institutional values, and functioning as instruments to strengthen university identity and encourage active participation of academic community in achieving strategic institutional goals.Keywords: Persuasion Strategy, Rector's Speech, Rhetoric, Leadership Communication